The Improvement Chemical Property of Peatlands By fertilizer mussel shell ( Polymesoda erosa) To cultivation of the Sweet Corn - PRANATA, YUDA; BANDEM, PUTU DUPA; ZULFITA, DWI (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACTÂ This study aims to increase the pH of peat soil with shellfish flour and sweet corn crop yield on peatland. This research was conducted from March 19 to May 27 2018. This research was located in Sepakat II, Jl Reformasi Southeast Pontianak Subdistrict, Bansir Laut sub-district, UNTAN. The method used is Completely Randomized Design consisted of 5 treatments, 5 replications and each replication there were 3 plant samples. The treatments were as follows: without treatment (p0), 2.7 kg / plot (p1), 4.5 kg / plot, (p2) 6.3 kg / plot (p3), and 8.1 kg / plot (p4) . The variables observed in this study were root volume (cm3), dry weight (g), chlorophyll leaf (sped unit), plant height (cm), weight of cob with skin (g), weight of cob without skin (g), length of cob (cm), and the diameter of the cob (cm). The results showed that the usage of shellfish flour can increase the pH of peat soil, growth and yield of sweet corn on peatlands. This study did not find the best dose of shellfish flour for the growth and yield of sweet corn crops on peat soil but the effective dose of shellfish flour was found in sweet corn plants which were given shells 2.7 kg / plot.Keyword :Â shellfish flour, sweet corn, peat soil